2006
DOI: 10.1074/jbc.m508966200
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the C-terminal Domain of Enzyme I of the Escherichia coli Phosphotransferase System

Abstract: The bacterial phosphoenolpyruvate (PEP):glycose phosphotransferase system (PTS) mediates uptake/phosphorylation of sugars. The transport of all PTS sugars requires Enzyme I (EI) and a phosphocarrier histidine protein of the PTS (HPr). The PTS is stringently regulated, and a potential mechanism is the monomer/dimer transition of EI, because only the dimer accepts the phosphoryl group from PEP. EI monomer consists of two major domains, at the N and C termini (EI-N and EI-C, respectively). EI-N accepts the phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 33 publications
10
35
0
Order By: Relevance
“…The absence of proteolysis of EIC 270-575 is possibly due to its formation of an inclusion body before proteolysis took place during the overexpression. Our result is consistent with previous studies, 12,13 and indicates that keeping the linker helix is critical to confer proteolytic stability on EIC, while the short b bridge is important for proper folding of EIC. EIC 231-575 was stable during the purification using chromatography at a room temperature, and used for all experimental measurements hereafter.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The absence of proteolysis of EIC 270-575 is possibly due to its formation of an inclusion body before proteolysis took place during the overexpression. Our result is consistent with previous studies, 12,13 and indicates that keeping the linker helix is critical to confer proteolytic stability on EIC, while the short b bridge is important for proper folding of EIC. EIC 231-575 was stable during the purification using chromatography at a room temperature, and used for all experimental measurements hereafter.…”
Section: Resultssupporting
confidence: 83%
“…It has been reported that EIC can phosphorylate EIN from a biochemical assay using 32 P-PEP as a substrate. 12,16 When we added PEP to the mixture of EIN and EIC 231-575 after titration, we could immediately observe the chemical shift changes due to the phosphorylation reaction of EIN [red cross-peaks in Fig. 2(A)].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations